2020
DOI: 10.1002/jlb.4hi0420-098r
|View full text |Cite
|
Sign up to set email alerts
|

Frontline Science: Kindlin-3 is essential for patrolling and phagocytosis functions of nonclassical monocytes during metastatic cancer surveillance

Abstract: Nonclassical monocytes maintain vascular homeostasis by patrolling the vascular endothelium, responding to inflammatory signals, and scavenging cellular debris. Nonclassical monocytes also prevent metastatic tumor cells from seeding new tissues, but whether the patrolling function of nonclassical monocytes is required for this process is unknown. To answer this question, we utilized an inducible‐knockout mouse that exhibits loss of the integrin‐adaptor protein Kindlin‐3 specifically in nonclassical monocytes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Vascular patrolling by nonclassical monocytes occurs during both steady-state and inflammation and allows surveillance against invading pathogens and maintenance of vascular endothelial homeostasis (73). We reported that the vascular endothelium is activated in mice that have nonclassical monocytes unable to patrol the vasculature due to disruptions in integrin signaling (39). We hypothesize that both nMo1 and nMo2 monocytes patrol the vasculature, but this has yet to be tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular patrolling by nonclassical monocytes occurs during both steady-state and inflammation and allows surveillance against invading pathogens and maintenance of vascular endothelial homeostasis (73). We reported that the vascular endothelium is activated in mice that have nonclassical monocytes unable to patrol the vasculature due to disruptions in integrin signaling (39). We hypothesize that both nMo1 and nMo2 monocytes patrol the vasculature, but this has yet to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, CD14 dim CD16 + nonclassical monocytes (nMo) play critical roles in maintaining vascular homeostasis (39) and guard against viral pathogens (40). Shulte-Schrepping et al (14) recently reported depletion of all nonclassical monocytes in COVID-19.…”
Section: Intermediate and Nonclassical Monocytes Are Greatly Impactedmentioning
confidence: 99%
“…Murine non-classical monocyte (CX3CR1 high /Ly6C lo ) differentiation and survival depend on the orphan nuclear receptor Nr4a1, and hence, Nr4a1 KO mice have drastically less nonclassical monocytes without affecting IM or macrophage population. Non-classical monocytes prevent lung metastasis formation in the PyMT breast cancer murine model or induced by LLc or B16-F10 cancer cells injected intravenously [24,185,186,200]. Indeed, more lung metastases are observed in non-classical monocyte-depleted Nr4a1 KO mice upon cancer cells injected intravenously, and this is counteracted by Ly6C lo monocyte injection [24].…”
Section: Murine Non-classical Monocytes Prevent Lung Metastasismentioning
confidence: 99%
“…Non-classical monocyte infiltration into the lungs depends on Kindlin-3 since specific Kindlin-3 deletion in non-classical monocytes diminished their lung infiltration after cancer cell injection. This diminution is associated with an increase in lung metastases [200]. The interactions between cancer cells and non-classical monocytes and subsequent cancer cell material engulfment by nonclassical monocytes depend on CX3CR1 expression in nonclassical monocytes since these processes are decreased in CX3CR1 KO mice [24].…”
Section: Murine Non-classical Monocytes Prevent Lung Metastasismentioning
confidence: 99%
“…A recent study found that kindlin-3 directly interacts with paxillin and leupaxin through its F0 domain in the macrophage-like RAW 264.7 cell line; inhibition of kindlin-3 and paxillin/leupaxin interactions promoted cell motility and augmented phagocytosis ( 115 ). Another recent work reported that kindlin-3 was essential for patrolling function and cancer particle uptake of nonclassical monocytes during tumor metastasis to the lung ( 144 ).…”
Section: Integrin Modulation During Phagocytosismentioning
confidence: 99%